Employing industry experts as casual academics: value-adding or undervalued?. (3rd April 2021) - Clarke, Marilyn
ABSTRACT: Universities often employ industry experts in teaching roles to help bridge the theory – practice gap. As practitioners, they have the potential to make significant contributions to learning outcomes and to help prepare students for future employment. Using a case study approach based on qualitative data from the Business School in an Australian university, the study explores the reasons why industry experts take on an adjunct role, their experiences in that role, and the extent to which they perceive their contribution is valued within the university. The findings highlight the frustrations experienced by industry experts in their academic role. Participants were often frustrated by remuneration, lack of support, lack of communication and isolation from the wider university community. Drawing on human and social capital theory, the article shows how industry experts can add value by supporting students to develop their own human and social capital and by strengthening links between universities and industry. The paper concludes with suggestions for more effective people management practices ensuring that human and social capital contributions by industry experts are maximised for the benefit of all stakeholders.